Kepemimpinan Pelayanan Yesus Kristus Sebagai Model Bagi Pendidik Kristen dalam Mewujudkan Keharmonisan Sosial pada Tahun 2045 - Agustihana Delvryance; Cristian Seldjatem; Philipus Sunardi (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
This study examines the servant leadership of Jesus Christ as a model for Christian educators in an effort to realize social harmony towards 2045. Using a qualitative method involving literature analysis and in-depth interviews with a number of Christian educators, this study aims to explore the understanding and application of servant leadership principles in an educational context. The main focus of this research is to explore the values that Jesus taught, such as unconditional love, empathy, collaboration, and humility, and how these values can be applied in an educational setting. The research also analyzes the impact of applying these principles on the formation of students' socially sensitive characters and their ability to contribute positively to society. The results are expected to provide practical recommendations for Christian educators in creating an inclusive, safe and supportive learning environment. By forming students who are not only academically smart, but also have social awareness, it is hoped that they can become agents of change who bring positive impact in facing social challenges in the future. Through the application of Jesus' servant leadership, this research seeks to demonstrate the relevance of Christian values in creating a harmonious and equitable society in Indonesia in 2045.